Unraveling Fano noise and the partial-charge-collection effect in x-ray spectra below 1 keV - Rodrigues Ferreira Maltez, Dario Pablo (2023)
Fano noise, readout noise, and the partial-charge-collection (PCC) effect collectively contribute to the degradation of energy spectra in charge-coupled device (CCD) measurements, especially at low energies. In this work, the x rays produced by the fluorescence of fluorine (677 eV) and aluminum (1486 eV) were recorded using a Skipper-CCD, which enabled the readout noise to be reduced to 0.2e-. Based on an analytical description of photopeak shapes resulting from the convolution of the PCC effect and Fano noise, we achieved a precise characterization of the energy spectra. This description enabled us to disentangle and quantify the contributions from both Fano noise and the PCC effect. As a result, we determined the Fano factor and the electron-hole pair creation energy. Additionally, we estimated the PCC region of the sensor and, for the first time, experimentally observed the expected skewness of photopeaks at low energies.